Purple noon - Clément, René, 1913-1996; Delon, Alain, 1935-; Ronet, Maurice, 1927-1983; Highsmith, Patricia, 1921-1995 (Criterion collection (Blu-ray discs), 2012)
An adaptation of Patricia Highsmith's novel The Talented Mr. Ripley, this film stars Alain Delon as Tom Ripley, a duplicitous American charmer in Rome on a mission to bring his privileged acquaintance Philippe Greenleaf back to the United States; what initially seems a carefree tale of friendship soon morphs into a thrilling saga of seduction, identity theft, and murder. Bonus features include the original English language trailer, an archival interview with Alain Delon, and more.